Gendered Bodies : Toward a Women's Visual Art in Contemporary China - Cui, Shuqin (University of Hawaii Press, 2015)
Gendered Bodies introduces readers to women's visual art in contemporary China by examining how the visual process of gendering reshapes understandings of historiography, sexuality, pain, and space. When artists take the body as the subject of female experience and the medium of aesthetic experiment, they reveal a wealth of noncanonical approaches to art. The insertion of women's narratives into Chinese art history rewrites a historiography that has denied legitimacy to the woman artist. The gendering of sexuality reveals that the female body incites pleasure in women themselves, reversing the dynamic from woman as desired object to woman as desiring subject. The gendering of pain demonstrates that for those haunted by the sociopolitical past, the body can articulate traumatic memories and psychological torment. The gendering of space transforms the female body into an emblem of landscape devastation, remaps ruin aesthetics, and extends the politics of gender identity into cyberspace and virtual reality. The work presents a critical review of women's art in contemporary China in relation to art traditions, classical and contemporary. Inscribing the female body into art generates not only visual experimentation, but also interaction between local art/cultural production and global perception. While artists may seek inspiration and exhibition space abroad, they often reject the (Western) label "feminist artist." An extensive analysis of artworks and artists--both well- and little-known--provides readers with discursively persuasive and visually provocative evidence. Gendered Bodies follows an interdisciplinary approach that general readers as well as scholars will find inspired and inspiring